2008
DOI: 10.1021/ic8003307
|View full text |Cite
|
Sign up to set email alerts
|

Cyanoscorpionates: Synthesis and Crystallographic Characterization of One-Dimensional Cu(I) Coordination Polymers

Abstract: A new cyanoscorpionate ligand, hydrotris(3- t-butyl-4-cyanopyrazolyl)borate (Tp ( t-Bu,4CN )) is reported. Both Tp ( t-Bu,4CN ) and hydrotris(4-cyano-3-phenylpyrazolyl)borate (Tp (Ph,4CN)) form one-dimensional coordination polymers with Cu(I). The polymeric chains align to form channels which, in the case of Tp ( t-Bu,4CN ), can encapsulate solvent molecules, as evidenced by the characterization of one such polymer with encapsulated acetonitrile molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The dihedral angle (10), 2.665(10) Å ), and TlBp (t-Bu2) (2.632(12), 2.644(12) Å ) [22]. It is suggested that the increased Tl-N bond lengths are correlated with the electron-withdrawing nature of the cyano substituents, which is also observed for the related Tp Ph,4CN ligand [10,13]. The N-Tl-N bond angle in TlBp Ph,4CN is relatively smaller than those in TlBp 3t-Bu,5Me and TlBp 3t-Bu,5i-Pr , possibly due to the reduced steric demands of the phenyl substituents.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…The dihedral angle (10), 2.665(10) Å ), and TlBp (t-Bu2) (2.632(12), 2.644(12) Å ) [22]. It is suggested that the increased Tl-N bond lengths are correlated with the electron-withdrawing nature of the cyano substituents, which is also observed for the related Tp Ph,4CN ligand [10,13]. The N-Tl-N bond angle in TlBp Ph,4CN is relatively smaller than those in TlBp 3t-Bu,5Me and TlBp 3t-Bu,5i-Pr , possibly due to the reduced steric demands of the phenyl substituents.…”
Section: Resultsmentioning
confidence: 80%
“…The synthesis of 3-tert-butyl-4-cyanopyrazole has been reported [13]. A portion of 3-tert-butyl-4-cyanopyrazole (3.00 g, 20.13 mmol) was added to 0.54 g (10.11 mmol) of potassium borohydride in a round bottom flask (100 mL) equipped with a water-cooled condenser.…”
Section: Synthesis Of Kbp T-bu4cnmentioning
confidence: 99%
See 2 more Smart Citations
“…Thallium(I) complexes of 3-phenyl-4-cyanopyrazolyl and 3-t-butyl-4-cyanopyrazolyl borates show the familiar trigonal pyramidal structure, but while the phenyl substituted derivative shows some some association into coordination polymers via three cyano-nitrogen atoms interacting with the thallium ion [70], the t-butyl substituted derivative does not exhibit this interaction [71]. This has been rationalised on the basis of the greater steric bulk of the t-butyl group.…”
Section: Thalliummentioning
confidence: 99%